A Review of Tax Indirect Auditing Methods against Tax Evasion:The case of Greece - Stasinopoulos, D.; Kastanioti, C. (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper aims to review and analyze the indirect auditing methods that were applied in Greece for the first time at the beginning of 2012 as a tax auditing tool, for the more comprehensive identification of taxable items. By employing the use of indirect auditing methods (mark up method, net worth method, source & application of funds technique, unit & volume method and bank deposits/cash expenditure technique) an attempt is made to determine withheld taxable items, other than those measured by the tax forms and the official accounting books and taxpayers’ tax data, by utilising the information from various sources and bodies.The implementation of indirect auditing methods by the Tax Authority is gradually taking precedence among other methods as on the one hand it can provide more effective monitoring and disclosure of withheld tax liabilities and on the other hand it requires proper utilization and feedback with data and information from public and non-public bodies. The full digital restructuring, the systematisation of process flows, the automatic digital recording of data on a single platform and, above all, the multi-level 'interoperability' of the public services involved can become an 'effective tool' for the successful implementation of indirect auditing methods.